Students' Perceptions of Islam-Based Mathematics Learning - Septriansyah, Alif; Imamuddin, M.; Isnaniah, Isnaniah; Jaafar, Azhar; Langputeh, Suwannee; Azira, Voni (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2024)
Islamic-based mathematics learning is mathematics learning in an Islamic context. Learning mathematics in an Islamic context is expected for students to give more meaning to learning mathematics so that students are not afraid and negative suggestions do not arise. Good student perceptions of the teacher's teaching methods applied. This research uses qualitative descriptive research using purposive sampling techniques. The research subjects were class XII students at Senior High School 1 Sekayu West Sumatera Selatan. The instrument was a questionnaire based on Islamic aspects: religion, honesty, discipline, hard work, independence, curiosity, and communicativeness. Data were analyzed using descriptive statistical analysis. The results of the research show that a small number of students need the character to work hard in learning mathematics, which is caused by several factors, namely a lack of confidence in their abilities in learning mathematics and easily giving up on learning. Almost all students strongly agree with honesty because they understand that actions based on honesty will make them better and get the blessing of Allah SWT. The average percentage of students' perceptions regarding the application of Islamic values ​​in mathematics learning is 69% of the students strongly agree with the application of Islamic values ​​in class, 30%, almost half of the students agree with the application of Islamic values ​​in class, and 1%, a small portion disagree with the application of Islamic values ​​in class. Class on mathematics learning.